Morphometric analysis of T lymphocyte compartmentation in experimental autoimmune uveoretinitis. - Brown, E C (1989)
Experimental autoimmune uveoretinitis (EAU) in the Lewis rat is characterized by extensive infiltration of inflammatory cells into all compartments of the eye, only some of which become irreversibly damaged. The apparent differences in the pathogenic impact of inflammatory cells within different ocular compartments may suggest that different mechanisms underlie cellular infiltration and selective tissue destruction. In order to investigate the importance of T lymphocyte infiltration, we carried out a precise topographical and temporal analysis of T cell infiltration into five compartments of the eye using an improved method for the fixation of ocular tissue. Our study showed that T cell infiltration began in the ciliary body and was most numerous and sustained in this area during EAU. The peak of T cell infiltration into the retina was comparatively delayed and was of lesser magnitude. Analysis of T cell subsets revealed a tendency for the helper phenotype to predominant during the course of disease in all ocular compartments except the retina where both helper and cytotoxic/suppressor T cells were equally represented at the height of inflammation. We suggest that the pathogenetic impact of autoreactive lymphocytes in EAU depends on the accessibility of relevant tissue antigen and on local microenvironmental features of lymphocytic traffic within different ocular compartments.